Answer:
Step by step approach is as shown
Explanation:
- Consider the system Ax = 5z .............(1)
- Substitute (Ay) for z in equation (1)
- therefore, Ax = 5(Ay) ....................... (2)
- Hence the equation can also be written as Ax = A(5y) ................ (3)
recalling from commutative law that A + B = B + A and since A is a scalar, and from scalar multiplication of matrix.
- From equation (3) ; Ax = A(5y), it implies that x = 5y from comparison and as such if we compare with equation (2) where z = Ay
- therefore equation (2) can then be written as Ax = 5z, since there is consistency as such the the equation will also have a solution.